Predation of Micrurus cf. carvalhoi (Serpentes: Elapidae) by Cariama cristata (Cariamiformes: Cariamidae) - Marcelo Augusto Pereira Coelho Dias; Eduarda Melo de Abreu Vieira; Clodoaldo Lopes de Assis; Renato Neves Feio (Caldasia)
Predation upon Micrurus coral snakes is rarely seen, and therefore seldom reported. In this work we document a new predation record of Micrurus cf. carvalhoiby Cariama cristata, thus contributing with information about the trophic relationship between this venomous snake species and its predators.